Pengaruh Profitabilitas, Sales Growth dan Likuiditas Terhadap Nilai Perusahaan: (Studi Empiris Pada Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024) - Mubarokah, Nurfadilah; Triyani Budyastuti (Politeknik Raflesia Press, 2025)
Abstrak— Firm value reflects investor’s perception of a company’s performance and future prospects. The transportation and logistics sector in Indonesia plays a crucial role in supporting economic activities, but it is highly vulnerable to various global disruptions, such as the COVID-19 pandemic, geopolitical influences, and supply chain uncertainties. Additionally, this sector also faces internal challenges such as rising operational costs, changes in government regulations, and demands for efficiency from consumers and investors. Where previous research on the influence of profitability, sales growth, and liquidity on firm value has generated inconsistent results, further empirical testing is needed. This study aims to analyze the influence of profitability, sales growth, and liquidity on firm value in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Data collection was carried out using a purposive sampling technique, with a total sample of 110 data from 22 mining sector companies for 5 years. Firm value is measured using the Price-to-Book Value (PBV) ratio, profitability using Return on Assets (ROA), sales growth with annual revenue growth, and liquidity with the Current Ratio (CR). Data processing was carried out using SPSS Version 31.1.1. The findings of this study indicate that profitability have negative significant effect on firm value, Sales growth have a positive insignificant effect on firm value and liquidity demonstrates a positive significant influence on firm value. Keywords: Profitability, Sales Growth, Liquidity, Firm Value.